The B --> D*l nu form factor at zero recoil and the determination of |Vcb| - RYAN, SINEAD MARIE (Elsevier, 2002)
We summarize our lattice QCD study of the form factor at zero recoil in the decay ?B ! D???. After careful consideration of all sources of systematic uncertainty, we find, hA1 (1) = 0.913+24 ?17 +17 ?30, where the first uncertainty is from statistics and fitting while the second combined uncertainty is from all other systematic effects.
PUBLISHED
Keywords: Pure & Applied Mathematics